A novel Artificial Neural Network training method combined with Quantum Computational Multi-Agent System theory. (27th January 2009) - Meng, Xiangping; Wang, Jianzhong; Pi, Yuzhen; Yuan, Quande
Artificial Neural Networks (ANNs) are powerful tools that can be used to model and investigate various complex and non-linear phenomena. In this study, we construct a new ANN, which is based on Multi-Agent System (MAS) theory and quantum computing algorithm. All nodes in this new ANN are presented as Quantum Computational (QC) agents, and these agents have learning ability. A novel ANN training method was proposed via implementing QCMAS reinforcement learning. This new ANN has powerful parallel-work ability and its training time is shorter than classic algorithm. Experiment results show that this method is effective.